NLRP12-expressing dendritic cells mediate both dissemination of infection and adaptive immune responses in visceral leishmaniasis - Diogo Garcia Valadares; Owen Scott Clay; Yani Chen; Breanna Mary Scorza; Suzanne Louise Cassel; Fayyaz Shiraz Sutterwala; Mary Edythe Wilson (iScience, 2023)
Summary: The NLR protein NLRP12 contributes to innate immunity, but the mechanism remains elusive. Infection of Nlrp12−/− or wild-type mice with Leishmania infantum led to aberrant parasite tropism. Parasites replicated to higher levels in livers of Nlrp12−/− mice than in the livers of WT mice and failed to disseminate to spleens. Most retained liver parasites resided in dendritic cells (DCs), with correspondingly fewer infected DCs in spleens. Furthermore, Nlrp12−/− DCs expressed lower CCR7 than WT DCs, failed to migrate toward CCL19 or CCL21 in chemotaxis assays, and migrated poorly to draining lymph nodes after sterile inflammation. Leishmania-infected Nlpr12−/− DCs were significantly less effective at transporting parasites to lymph nodes than WT DCs. Consistently, adaptive immune responses were also impaired in infected Nlrp12−/− mice. We hypothesize that Nlrp12-expressing DCs are required for efficient dissemination and immune clearance of L. infantum from the site of initial infection. This is at least partly due to the defective expression of CCR7.